Data Consistency in IMF Publications : Country Staff Reports Versus International Financial Statistics - Cady, John (IMF Working Papers; Working Paper ;, 2005)
Data published in IMF country staff reports and International Financial Statistics (IFS) may differ for identical variables and, at times, users may be unaware of the reasons for these differences and lack the information needed to permit reconciliation. Such discrepancies stem principally from differences in the objectives of IMF country staff reports and their data requirements, on the one hand, and IFS, on the other. This paper presents the results of a study of the consistency of annual data on core statistical indicators required for Fund surveillance presented in the IMF's IFS and a sample of recently published Article IV consultation reports. The paper finds a significant incidence of apparent discrepancies for similarly defined variables.